Which Source Possesses the Best Data on the Empirical Aspects of Criminal Events? A Theory of Opportunity and Necessary Conditions. Issue 12 (2nd December 2019) - Jacques, Scott
ABSTRACT: Offenders and nonoffenders possess valuable information about crime. But which possesses the best data? This is a complex issue, so I narrow my focus to data on empirical aspects of criminal events. Drawing on the necessary conditions perspective, I theorize that a source's possession 1) of data varies directly with its involvement in cases; 2) of representative data varies inversely with nonrandom involvement in cases and nonrandom siphoning off from the larger group to which it belongs; and, 3) of accurate data varies inversely with time since involvement in cases. Those general principles suggest that offenders, especially active ones, possess the most data, representative data, and accurate data on empirical aspects of criminal events. I conclude by discussing the implications of those general principles for observation research, sources' possession of subjective data, and their possession of empirical data on other criminological events, specifically victimization and policing.